Hubungan Antara Lama Kerja Dengan Force Expiratory Volume In One Second Pada Operator Stasiun Pengisian Bahan Bakar Umum (SPBU) - Wahyudi, Latif, Isnaini Herawati, S.Fis.,Ftr.,M.Sc, Totok Budi Santoso , S.Fis , MPH (2015)
Background : Respiratory can decrease the functional ability of lungs system. One of the major causes of this problem is the air pollution. Indonesia is considered as the third highest polluted country in the world and around 70% of the pollution caused by vehicle gas emission. Lungs have function as our respiratory organ to change the air we breathe through inhaling the air from the atmosphere and exhaling it from the veolar system. Inhalation of harmful pollutants can cause a variety of effects for the lungs and decreased the lungs function through various pathophysiological processes. Pulmonary or lungs test was done by using diagnostok called a spirometer. Methods : This research type is a case control study (survey) concerning analytical risk factor studied by using retrospective approach. The population of this study is 36 people of the gas station operator of Rosalia Indah Group. FEV1 was measured by using a spirometer. Result : The results of data analysis done by using chi square test showed that P <0.05. The relationship of analysis showed Odds Ratio (OR) value of 10.000, it means that respondent with longer working period are 10 times resistant to loss FEV1 than respondent with shorter working period. Conclusions and suggestions : There is significant correlation between the length of work with FEV1 at the gas station operator. With the value of the relationship Odds Ratio (OR) 10.000, it means that respondent with longer working period are 10 times resistant to loss FEV1 than respondent with shorter working period. There is a significant result toward the conditions to create better quality life of the gas station operator and physiotherapy plays a vital role as a preventive action for their healthy life.